Differential Progression of Motor Dysfunction Between Male and Female Fragile X Premutation Carriers Reveals Novel Aspects of Sex-Specific Neural Involvement - Loesch, Danuta Z.; Tassone, Flora; Atkinson, Anna; Stimpson, Paige; Trost, Nicholas; Pountney, Dean L.; Storey, Elsdon (Frontiers in Molecular Biosciences, 2021)
Expansions of the CGG repeat in the non-coding segment of the FMR1 X-linked gene are associated with a variety of phenotypic changes. Large expansions (>200 repeats), which cause a severe neurodevelopmental disorder, the fragile x syndrome (FXS), are transmitted from the mothers carrying smaller, unstable expansions ranging from 55 to 200 repeats, termed the fragile X premutation. Female carriers of this premutation may themselves experience a wide range of clinical problems throughout their lifespan, the most severe being the late onset neurodegenerative condition called “Fragile X-Associated Tremor Ataxia Syndrome” (FXTAS), occurring between 8 and 16% of these carriers. Male premutation carriers, although they do not transmit expanded alleles to their daughters, have a much higher risk (40–50%) of developing FXTAS. Although this disorder is more prevalent and severe in male than female carriers, specific sex differences in clinical manifestations and progress of the FXTAS spectrum have been poorly documented. Here we compare the pattern and rate of progression (per year) in three motor scales including tremor/ataxia (ICARS), tremor (Clinical Tremor Rating scale, CRST), and parkinsonism (UPDRS), and in several cognitive and psychiatric tests scores, between 13 female and 9 male carriers initially having at least one of the motor scores ≥10. Moreover, we document the differences in each of the clinical and cognitive measures between the cross-sectional samples of 21 female and 24 male premutation carriers of comparable ages with FXTAS spectrum disorder (FSD), that is, who manifest one or more features of FXTAS. The results of progression assessment showed that it was more than twice the rate in male than in female carriers for the ICARS-both gait ataxia and kinetic tremor domains and twice as high in males on the CRST scale. In contrast, sex difference was negligible for the rate of progress in UPDRS, and all the cognitive measures. The overall psychiatric pathology score (SCL-90), as well as Anxiety and Obsessive/Compulsive domain scores, showed a significant increase only in the female sample. The pattern of sex differences for progression in motor scores was consistent with the results of comparison between larger, cross-sectional samples of male and female carriers affected with the FSD. These results were in concert with sex-specific distribution of MRI T2 white matter hyperintensities: all males, but no females, showed the middle cerebellar peduncle white matter hyperintensities (MCP sign), although the distribution and severity of these hyperintensities in the other brain regions were not dissimilar between the two sexes. In conclusion, the magnitude and specific pattern of sex differences in manifestations and progression of clinically recorded changes in motor performance and MRI lesion distribution support, on clinical grounds, the possibility of certain sex-limited factor(s) which, beyond the predictable effect of the second, normal FMR1 alleles in female premutation carriers, may have neuroprotective effects, specifically concerning the cerebellar circuitry.